Struggle for Inclusion of Genderqueer Identities (Solukhumbu Multiple Campus Research Journal, 2024)
This study aims to explore the challenges and current status of social inclusion within the genderqueer (LGBT) community. For this purpose, ten samples were taken for interview, participatory observation, and field notes. The data were interpreted using qualitative explanatory design and reflective cum reflexive techniques. Confidentiality is also maintained through using pseudonyms in the study. The theory of recognition and the queer theory were used to make a discussion more trustworthy. The literature shows that there were several indigenous provisions and practices on homosexuality. The empirical data shows that gender identity, relationships, social exclusion, effects of consumerism, school enrolment and environment, employment, rental discrimination, polysexuality, sexual violence, social exclusion, and legalization of same-sex marriage or partnership surfaced as the major issues of LGBT in Nepal. The data also show that different people have different levels of exclusion. The issue of identity vs. relationship is a major threat to LGBT’s inclusion. However, they were less worried about their own identity than their social relationships. Hence, they were compelled to maintain double-standard identities because they feared relationship breakup. In order to resolve these issues, it is necessary to come up with policies and laws that take into consideration the gender and sexuality of the individuals, engage in the formulation of duty and rights based social frameworks, establish systems of collective identities and combat genderism, social stereotypes and superstitions. Moreover, embedding Aboriginal ethical and social values, questioning and remaking the hetero-patriarchy, ensuring targeted budget support, allowing and encouraging a more positive environment for inclusive education, creating inclusiveness of the LGBTQ+ community in school curricula and environments are vital steps in the struggle for inclusion and equity.